It’s not the economy, stupid : Competition between Finnish right-wing parties analysed using multinomial logistic regression in the context of the 2023 parliamentary election - Engström, Richard (My University, 2026)
In the year 2023 Finland held parliamentary election. In this election the Finns Party got 46 seats, which was the best election result ever for the party. In prior research it has been found that in the 2020s Finns Party’s voters have shifted right on the right-left axis. At the same time, previous research has found that critical views on immigration partly explain the voting of Finns Party. This thesis examines how views on immigration, multiculturality and sexual minorities affect the voters’ likelihood of choosing the Finns Party. As the theoretical framework this thesis utilizes the idea of cultural backlash, which states that voters who hold negative views on the topics mentioned above are more likely to vote for a populist party. This effect is examined in relation to all other parties that won seats in the 2023 parliamentary election, with the exception of the Movement Now party. At the focus of the thesis is Finns Party against National Coalition Party and the Centre Party that, along with the Finns Party, are right-wing parties. The analysis of this thesis was done by using a latent variable in multinomial logistic regression. The analysis indicates that Finns Party fulfils the assumption of the theoretical frame; voters who have negative feelings about the topics mentioned above are more likely to choose the Finns Party compared to other parties in the analysis. This finding was also in the model containing only the right-wing parties.

Vuonna 2023 Suomessa järjestettiin eduskuntavaalit. Näissä vaaleissa Perussuomalaiset saivat 46 paikkaa, mikä on puoleen paras vaalitulos koskaan. Aikaisemmassa tutkimuksessa on havaittu, että 2020-luvulla perussuomalaisten äänestäjät ovat siirtyneet oikeammalle vasemmisto-oikeisto-akselilla. Samalla on myös havaittu, että kriittiset näkemykset maahanmuuttoon ovat selittämässä perussuomalaisten äänestämistä. Tässä tutkielmassa tarkastellaan, miten maahanmuuttonäkemykset sekä suhtautuminen monikulttuurisuuteen ja seksuaalivähemmistöihin vaikuttavat äänestäjän todennäköisyyteen valita Perussuomalaiset. Tutkielman teoreettisena viitekehyksenä on kulttuurinen takaisku, jonka perusteella negatiivisesti yllä mainittuihin asioihin suhtautuvat äänestävät todennäköisemmin populistista puoluetta. Tätä vaikutusta tarkastellaan suhteessa muihin vuonna 2023 eduskuntavaaleissa läpi menneisiin puolueisiin, pois lukien Liike Nyt. Tarkastelun keskiössä on Perussuomalaiset suhteessa Kansalliseen Kokoomukseen ja Suomen Keskustaan, jotka ovat Perussuomalaisten ohella oikeistopuolueita. Tutkielmassa analyysi toteutettiin käyttämällä latenttia muuttujaa nominaalisessa regressiossa. Analyysin perusteella Perussuomalaiset toteuttaa teoreettisen viitekehyksen tarjoamaa oletusta siitä, että negatiivisesti yllä mainittuihin asioihin suhtautuvat äänestävät todennäköisemmin Perussuomalaisia kuin muita tarkastelussa olleita puolueita. Tämä havainto nähdään myös oikeistopuolueiden keskinäisessä vertailussa.
Keywords: voting behaviour; parliamentary election; populism; attitudes; right-wing parties; äänestyskäyttäytyminen; eduskuntavaalit; populismi; asenteet; oikeistopuolueet